2011
DOI: 10.1007/s00436-011-2569-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Eimeria bovis and Eimeria zuernii in German cattle herds and factors influencing oocyst excretion

Abstract: The present study was designed to investigate the prevalence of the pathogenic coccidia species Eimeria bovis and Eimeria zuernii in shed-reared animals in German dairy and fattening facilities. Samples were obtained from 65 cattle farms distributed randomly across all the regions of Germany regardless of the occurrence of clinical problems. The samples were obtained rectally. Faecal consistency and the total number of oocysts per gram of faeces (OPG) were determined, along with the OPG values for E. bovis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
13
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 16 publications
6
13
2
3
Order By: Relevance
“…In this study two cattle species (E. bovis and E. auburnensis) were detected in sheep. These species were observed in previous studies in their specific host, where Ibrajim et al (26) recorded E. bovis 25.84% and E. auburnensis 7.78%, in Saudi Arabia in Subclinical bovine coccidiosis, also Bangoura et al (27) showed E. bovis was more effective and highly pathogenic.…”
Section: Discussionsupporting
confidence: 63%
“…In this study two cattle species (E. bovis and E. auburnensis) were detected in sheep. These species were observed in previous studies in their specific host, where Ibrajim et al (26) recorded E. bovis 25.84% and E. auburnensis 7.78%, in Saudi Arabia in Subclinical bovine coccidiosis, also Bangoura et al (27) showed E. bovis was more effective and highly pathogenic.…”
Section: Discussionsupporting
confidence: 63%
“…This finding has been widely observed (Lassen et al 2009; Bangoura et al 2012; Dong et al 2012; Rehman et al 2012), and it is likely that an age-related immune effect occurs for this parasite (Fiege et al 1992). Protective immunity is generally dose dependent and is usually against infection with a homologous species (Rose 1971).…”
Section: Discussionsupporting
confidence: 58%
“…Outro aspecto que chama atenção é o fato de que, apesar de E. zuernii e E. bovis serem relatadas como as espécies mais prevalentes em bovinos, trabalhos realizados no Brasil, Tanzânia, Turquia, Pakistão, Alemanhã, Irã e Estados Unidos (Rebouças et al 1994, Chibunda et al 1997, Cicek et al 2007, Almeida et al 2011, Bruhn et al 2011, Rehman et al 2011, Bangoura et al 2012, Bahrami & Alborzi 2013, Lucas et al 2014, Rodrigues 2014, reportam que E. bovis foi a espécie mais prevalente nos rebanhos. Tais resultados fizeram com que estes pesquisadores descrevessem E. bovis como a mais frequente em bovinos no mundo.…”
Section: Discussionunclassified